2004
DOI: 10.1111/j.0022-202x.2004.22605.x
|View full text |Cite
|
Sign up to set email alerts
|

Dystroglycan in Skin and Cutaneous Cells: β-Subunit Is Shed from the Cell Surface

Abstract: In skin, hemidesmosomal protein complexes attach the epidermis to the dermis and are critical for stable connection of the basal epithelial cell cytoskeleton with the basement membrane (BM). In muscle, a similar supramolecular aggregate, the dystrophin glycoprotein complex links the inside of muscle cells with the BM. A component of the muscle complex, dystroglycan (DG), also occurs in epithelia. In this study, we characterized the expression and biochemical properties of authentic and recombinant DG in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 45 publications
3
72
0
Order By: Relevance
“…Therefore, the specific cleavage produced by MMP-9 at the amino acid positions 715-716, overlapping with the end of the a-DG binding epitope, removes the a-DG binding epitope impairing the a-DG/b-DG interface. This might explain the presence of the 30 kDa b-DG fragment, which con- tains the entire cytosolic domain, produced by MMP-9 in healthy tissues, such as peripheral nerve, bladder, lung, kidney (10) and in normal human keratinocytes (11). Indeed, the b-DG ectodomain shedding produced by MMP-9 removes the a-DG binding epitope interrupting the link between the extracellular matrix and the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the specific cleavage produced by MMP-9 at the amino acid positions 715-716, overlapping with the end of the a-DG binding epitope, removes the a-DG binding epitope impairing the a-DG/b-DG interface. This might explain the presence of the 30 kDa b-DG fragment, which con- tains the entire cytosolic domain, produced by MMP-9 in healthy tissues, such as peripheral nerve, bladder, lung, kidney (10) and in normal human keratinocytes (11). Indeed, the b-DG ectodomain shedding produced by MMP-9 removes the a-DG binding epitope interrupting the link between the extracellular matrix and the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known from the literature that b-DG is a target for MMP-9, whose enzymatic activity produces a typical 30 kDa b-DG fragment detected both in pathological, as well as in physiological conditions (9)(10)(11). It was also demonstrated that the 30 kDa fragment lacks the ectodomain, as it can be still detected by a monoclonal antibody directed against the C-terminal cytosolic region of b-DG (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence has grown for the importance of non-integrin receptors such as dystroglycan (DG), a ubiquitously expressed cell-surface receptor responsible for crucial interactions between ECM and the cytoplasmic compartment, whose expression has been shown to be reduced or lost in a variety of human cancer cell lines and primary tumors. 15,18,19,[21][22][23][24] DG is expressed in podocytes at the base of foot processes and DG-laminin interaction has been shown to be essential for epithelium development in kidney organ culture (Durbeej, 1995 #969). Moreover, it has been demonstrated that the DG complex undergoes changes in human glomerular diseases in which flattening of foot processes is directly associated with dissociation of laminin-DG complexes.…”
Section: Discussionmentioning
confidence: 99%
“…7,15,16 We and others recently demonstrated that DG expression, and mainly aDG, is reduced or lost in a variety of human cancer cell lines and primary tumors. 15,[17][18][19][20][21][22][23][24] A reduction in the expression levels of DG was shown to be most pronounced in high-grade diseases 17,21 and to have a prognostic significance in breast cancer patients. 21 We also recently demonstrated that expression of an exogenous DG cDNA inhibits proliferation of both normal and cancer breast epithelial cells and reduces the anchorage-independent growth and tumorigenicity of breast cancer cells, thus confirming an important role of this molecule in the maintenance of the transformed phenotype of these cells.…”
Section: Introductionmentioning
confidence: 99%